(untitled) (World Bulletin of Education and Learning, 2026)
This article analyzes the mystical ideas expressed in the works of two great representatives of Eastern mystical philosophy - Fariduddin Attor and Alisher Navoi - from a social and philosophical perspective. The authors’ works analyze the issues of human spiritual perfection, rapprochement with the Truth, and moral purification in society, highlighting their commonalities and differences.